Jerusalem artichoke (Helianthus tuberosus L.): A review of in vivo and in vitro propagation - Abdalla, N.; Domokos-Szabolcsy, É.; El-Ramady, H.; Hodossi, S.; Fári, M.; Ragab, M.; Taha, H. (International Journal of Horticultural Science, 2014)
Jerusalem artichoke (Helianthus tuberosus L.) is an old tuber crop with a recently renewed interest in multipurpose improvement. It is a perennial tuberous plant rich in inulin and is a potential energy crop. During food shortages in times of war Jerusalem artichoke received more attention by scientists and farmers because of its multiple uses as a vegetable, medicinal plant, forage plant and source for biofuel. The energy crisis of the 1970s motivated research on Jerusalem artichoke for biofuel as the aboveground plant biomass and the tubers can be used for this purpose. There are different methods to propagate Jerusalem artichoke using tubers, rhizomes, slips (transplants derived from sprouted tubers), stem cuttings, seeds and tissue culture. So, this review was presented to highlight on propagation of Jerusalem artichoke via in vivo and in vitro techniques.